2020
DOI: 10.1084/jem.20192152
|View full text |Cite
|
Sign up to set email alerts
|

Japanese encephalitis virus–primed CD8+ T cells prevent antibody-dependent enhancement of Zika virus pathogenesis

Abstract: Cross-reactive anti-flaviviral immunity can influence the outcome of infections with heterologous flaviviruses. However, it is unclear how the interplay between cross-reactive antibodies and T cells tilts the balance toward pathogenesis versus protection during secondary Zika virus (ZIKV) and Japanese encephalitis virus (JEV) infections. We show that sera and IgG from JEV-vaccinated humans and JEV-inoculated mice cross-reacted with ZIKV, exacerbated lethal ZIKV infection upon transfer to mice, and promoted vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…It has been shown in Dengue virus infection, efficient CD8 T cells response is sufficient to inhibit ADE in infected mice. Our present study together with previous findings (18,24) all suggest that cross-reactive JEV-specific CD8 T cells are protective to ZIKV infection in wild-type mice that are not HLA-transgenic (18,19,25). Thus, JEV vaccine can be clinically used for the prevention of ZIKV infection and also is at low risk of ADE induction in immune-competent humans.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It has been shown in Dengue virus infection, efficient CD8 T cells response is sufficient to inhibit ADE in infected mice. Our present study together with previous findings (18,24) all suggest that cross-reactive JEV-specific CD8 T cells are protective to ZIKV infection in wild-type mice that are not HLA-transgenic (18,19,25). Thus, JEV vaccine can be clinically used for the prevention of ZIKV infection and also is at low risk of ADE induction in immune-competent humans.…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, CD8 T cells in JEV-vaccinated and JEV-exposed healthy human subjects cross-react with DVs ( 16 , 17 ) and other flaviviruses. Furthermore, Recent studies have revealed that murine MHC I-restricted CD8 T cells from mice infected with JEV or vaccine strain are indeed cross-reactive with ZIKV ( 18 , 19 ). These evidences suggest JEV vaccination may elicit cross-reactive T cell immunity against ZIKV and thereby affect ZIKV pathogenesis in humans.…”
Section: Introductionmentioning
confidence: 99%
“…(1) In vitro serological experiment ELISA testing proved that sera of JEV-immune mice or humans contained ZIKV crossreactive antibodies, and He, et al demonstrated that the titers of JEV antibodies were positively correlated with the titers of ZIKV cross-reactive antibodies in ZIKV non-endemic areas [6,42]. However, few cross-reactive NAbs against ZIKV were present in JEV-immune sera, and JEV-immune human and mouse sera could induce ADE of ZIKV in vitro [6,43].…”
Section: The Impact Of Prior Jev Immunity On Zikv Infectionmentioning
confidence: 99%
“…(2) In vivo mouse model By sequential infection of JEV-ZIKV and passive administration of JEV antisera in the ifnar −/− mouse model, Zhang, et al reported that the immune history of JE LAV could protect the mice against ZIKV infection without the mediation of cross-reactive antibodies [6]. Passive transfer of highly diluted sera of JE LAV immune humans or rabbits exacerbated ZIKV infection in the ifnar1 transiently blockaded mouse model [42,43]. Additionally, neonates of JEV-immune female mice showed higher mortality and viremia level than neonates of non-immune mice when challenged with ZIKV [43], suggesting that the anti-JEV IgG antibody from pregnant mice caused ADE of ZIKV in neonates.…”
Section: The Impact Of Prior Jev Immunity On Zikv Infectionmentioning
confidence: 99%
“…Sequential infection by two different DENV serotypes or by ZIKV followed by DENV is known to be a major risk factor for severe dengue, in part due to the phenomenon of Ab-dependent enhancement of infection induced by pre-existing anti-flaviviral immunity ( Halstead, 2007 ; Katzelnick et al, 2017 , 2020 ; Salje et al, 2018 ). The robustness of the immune response elicited by prior DENV exposure can influence ZIKV infection outcome, through T cell-mediated cross-protection against ZIKV and antibody-mediated enhancement of ZIKV pathogenesis ( Bardina et al, 2017 ; Chen et al, 2020 ; Gordon et al, 2019 ; Pedroso et al, 2019 ; Rathore et al, 2019 ; Regla-Nava et al, 2018 ; Rodriguez-Barraquer et al, 2019 ; Valentine et al, 2020 ; Wen et al, 2017a , 2017b , 2020 ). The present study reveals that ZIKV can readily adapt to enhance its virulence not only in a naive host but also in the presence of pre-existing cross-protective DENV immunity.…”
Section: Discussionmentioning
confidence: 99%